Wheat grain yield and nitrogen uptake as influenced by fertilizer placement depth. Issue 1 (4th March 2020) - Bryant‐Schlobohm, Ryan; Dhillon, Jagmandeep; Wehmeyer, Gwendolyn B.; Raun, William R.
Abstract: Global nitrogen use efficiency (NUE) for cereal production is estimated to be only 33%. Providing producers with efficient methods to increase the effectiveness of their N applications is integral to agricultural sustainability and environmental quality. This study was conducted to evaluate the effect of urea ammonium nitrate (UAN) injected at different depths on grain yield and uptake of N in grain. Liquid UAN (28–0–0) was applied in bands at depths of 5 and 10 cm, along with surface applications, all at various N rates around Feekes growth stage 5. Placement depth had the most significant impact on yield at low N rates. Subsurface application at 10 cm was most beneficial in low N no‐till (NT) soils, whereas surface treatments produced higher yields in low N environments of conventional till (CT) systems. Three of the four locations experienced higher rates of N uptake from subsurface applications when compared with surface treatments. No difference in grain N uptake was apparent between application depths of 5 and 10 cm. Subsurface N applications were beneficial in reducing rates of ammonia volatilization from urea‐based fertilizers. While there was no clear separation between 5 and 10 cm application depths, subsurface depths of 10 cm provide the most significant promise in benefiting yield in low N environments of NT soils and increasing grain N across CT and NT systems.